Identification of the Escherichia coli sohB gene, a multicopy suppressor of the HtrA (DegP) null phenotype. - Baird, L (1991)
We cloned and sequenced the sohB gene of Escherichia coli. The temperature-sensitive phenotype of bacteria that carry a Tn10 insertion in the htrA (degP) gene is relieved when the sohB gene is present in the cell on a multicopy plasmid (30 to 50 copies per cell). The htrA gene encodes a periplasmic protease required for bacterial viability only at high temperature, i.e., above 39 degrees C. The sohB gene maps to 28 min on the E. coli chromosome, precisely between the topA and btuR genes. The gene encodes a 39,000-Mr precursor protein which is processed to a 37,000-Mr mature form. Sequencing of a DNA fragment containing the gene revealed an open reading frame which could encode a protein of Mr 39,474 with a predicted signal sequence cleavage site between amino acids 22 and 23. Cleavage at this site would reduce the size of the processed protein to 37,474 Mr. The predicted protein encoded by the open reading frame has homology with the inner membrane enzyme protease IV of E. coli, which digests cleaved signal peptides. Therefore, it is possible that the sohB gene encodes a previously undiscovered periplasmic protease in E. coli that, when overexpressed, can partially compensate for the missing HtrA protein function.